Perception of pregnant women regarding the use of medicinal plants in the city of Cuité-PB (Research, Society and Development, 2020)
Objective: to evaluate the knowledge of pregnant women regarding the use of medicinal plants in the municipality of Cuité-PB. Methodology: consists of a quantitative research, with a descriptive and cross-sectional typology, carried out in the Family Health Strategies and Reference Center for Social Assistance in the municipality of Cuité-PB, with 50 pregnant women from February to March 2019. Results: it was possible to verify the knowledge of pregnant women about medicinal plants used in general, their form of acquisition, indication, and their use in the gestational period, showing risks, contraindications and guidance of health professionals regarding the theme. Thus, it was realized that scientific knowledge should prevail over collective common sense, due to the lack of reliable information about the use of plants as a form of treatment, especially during pregnancy, since 36% of the interviewees said they had guidance on this practice during pregnancy monitoring. Conclusion: therefore, understanding the view of pregnant women was of great relevance, since the use of medicinal plants in the pregnancy period poses risks to fetal development and maternal health. Finally, guidance by health professionals is essential to prevent risks and health problems, strengthening and valuing the Integrative and Complementary Practices in the Unified Health System.